Annotated list of flora of the ecological settlement «Raduha» (Kherson Region, Ukraine). (CHORNOMORSKI BOTANICAL JOURNAL, 2022)
The list of vascular plant species of the ecological settlement «Raduha» is given in the article. In 2020–2021, we conducted a comprehensive study of the flora of the settlement, supported by its founder Oleksii Ursulenko. The ecological settlement is administratively located within the Oleshky Territorial Community of the Kherson district of the Kherson region, in the western outskirts of the village of Sahy. The eco-settlement has an area of 30 hectares on the Oleshky sand arena. Wavy sands cover the territory with a slight natural elevation difference. The height of the dunes and the depth of the blowing pits do not exceed 1 m. The dominant types of natural vegetation within the area are psammophyte steppes, meadows and forest groves in the depressions. The main focus of the settlement is to spread the philosophy of good nutrition and healthy living, as well as to conduct educational seminars and health practices. The territory is slightly influenced by anthropogenic impact and differs by the high level of preservation of natural ecosystems. The studied flora of the ecological settlement "Raduga" includes 259 species of vascular plants from 170 genera, 52 families, three classes, and two divisions. Most species are herbaceous plants, while 20 species represent woody plants. Most woody plants are cultivated introduced species, which easily spread spontaneously in the region, in particular: ‘Armeniaca vulgaris, different varieties of Malus domestica, Prunus cerasifera, P. domestica, etc. Among them, there are one liana species and five species of shrubs. On the territory of the eco-settlement "Raduha", 46 species are melliferous plants, and 63 species are medicinal plants. In the list, there are also protected species: five species listed in the Red Data Book of Ukraine – Alyssum savranicum, Anacamptis palustris, Betula borysthenica, Centaurea breviceps, Stipa borysthenica, one endangered species of the CITES – again Anacamptis palustris, and one endangered species on both of the European Red List and IUCN Red List – Agropyron dasyanthum. The plant communities with a dominance of Stipa borysthenica and Betula borysthenica are protected by the Green Book of Ukraine. Pontic sandy steppes are listed in Resolution 4 of the Bern Convention (as habitat E1.12) and in the European Red List of Habitats (habitat E1.1a).
Keywords: ecological settlement «Raduga», vascular plants, Oleshky sand massif.